2019
DOI: 10.1002/ardp.201800358
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HIV‐TB coinfection by developing novel piperidin‐4‐substituted imines: Design, synthesis, in vitro and in silico studies

Abstract: Tuberculosis is the "Achilles heel" of the human immunodeficiency (HIV) ministration.HIV-positive people are 16-27 times more prone to contract tuberculosis. But the adverse interaction between antiretroviral drugs and antitubercular drugs has made it necessary to look for a single drug regimen for HIV-TB coinfection. Piperidine derivatives have been reported as anti-HIV and anti-TB agents. This inspired us to design, synthesize, and characterize a series of 3,5-bis(furan-2-ylmethylidene)piperidin-4-substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…This work is in continuation of our previous reported piperidone derivatives as potential anti-HIV/TB agents (Kumar et al 2019). In the present work, we have designed non-covalent DprE1 inhibitors by developing an e-Pharmacophore model by using the receptor-ligand interactions of DprE1 with 2-carboxyquinoxalines as reported in its X-ray crystal structure (Neres et al 2015).…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…This work is in continuation of our previous reported piperidone derivatives as potential anti-HIV/TB agents (Kumar et al 2019). In the present work, we have designed non-covalent DprE1 inhibitors by developing an e-Pharmacophore model by using the receptor-ligand interactions of DprE1 with 2-carboxyquinoxalines as reported in its X-ray crystal structure (Neres et al 2015).…”
Section: Introductionsupporting
confidence: 84%
“…From this study, we can conclude that the piperidine ring substituted with furylidene rings and methyl benzimidazole ring showed potent antitubercular activity. But if we compare the antitubercular activity of parent compounds without substitution at the 4th position of piperidine ring like R2, R3, R8, R9 and R11 for which the corresponding compounds are B2, B3, B8, B9 and B11, we found that the activity was same in both the cases (Kumar et al 2019). The compounds like B4, B5, B6 and B12 were twice less potent than their unsubstituted derivatives.…”
Section: In Vitro Antitubercular Evaluationmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, 23 was more active in ex vivo assays than the hybrid 22 (Figure 18) [102]. Kumar and coworkers [105] identified piperidine as a privileged structure with properties anti-HIV and anti-MTB. Kumar et al found that 1,4-disubstituted piperidine derivatives exhibited high anti-MTB activity [106][107][108] and moderate inhibition activity against HIV-1 [109].…”
Section: Mtb Strainmentioning
confidence: 99%
“…TB remains the leading presenting opportunistic infection among people with HIV infection, and HIV-positive individuals are 16 to 27 times more likely to contract TB than HIV-negative individuals. [ 1 ] Moreover, TB is the leading cause of death from infectious diseases globally, causing approximately 214,000 deaths among HIV-positive people globally in 2020 (up from 209,000 in 2019) according to the World Health Organization. [ 2 ] HIV strikingly increases the risk of progression to active TB and the mortality associated with TB.…”
Section: Introductionmentioning
confidence: 99%